Pengaruh Disiplin dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Indralaya Agro Lestari Muara Enim - Pratama, Muhammad Ade; Kosim, Belliwati; Permana, Arraditya (PT Maju Malaqbi Makkarana, 2025)
This study aims to determine the effect of work discipline and work environment on employee performance at PT. Indralaya Agro Lestari Muara Enim. The type of research used is associative research with a quantitative approach. Data collection was carried out through the distribution of questionnaires to respondents. The population in this study consisted of 110 employees, with a sample of 86 people selected proportionally. Data analysis was performed using multiple linear regression analysis, as well as F-test, t-test, and coefficient of determination. The results showed that both simultaneously and partially, work discipline and work environment had a positive and significant effect on employee performance. This is proven by the regression equation Y = 2.012 + 0.570X₁ + 0.242X₂. Simultaneously, the F-value of 141.088 is greater than the F-table value of 3.11 with a significance level of 0.000 < 0.05, indicating a significant influence of discipline and work environment on performance. Partially, work discipline significantly affects performance (t-value = 7.862 > t-table = 1.988; sig. 0.000), as does the work environment (t-value = 3.582 > t-table = 1.988; sig. 0.000). The coefficient of determination value of 0.767 indicates that 76.7% of the variation in employee performance can be explained by these two variables, while the remaining 23.3% is influenced by other factors outside this study.